Prenatal alcohol exposure contributes to negative pregnancy outcomes by altering fetal vascular dynamics and the placental transcriptome. (9th May 2022) - Pinson, Marisa R.; Tseng, Alexander M.; Adams, Amy; Lehman, Tenley E.; Chung, Karen; Gutierrez, Jessica; Larin, Kirill V.; Chambers, Christina; Miranda, Rajesh C.; ,
Abstract: Background: Prenatal alcohol exposure (PAE) has been shown to alter fetal blood flow in utero and is also associated with placental insufficiency and intrauterine growth restriction (IUGR), suggesting an underlying connection between perturbed circulation and pregnancy outcomes. Methods: Timed‐pregnant C57/BL6NHsd mice, bred in‐house, were exposed by gavage on gestational day 10 (GD10) to ethanol (3 g/kg) or purified water, as a control. Pulse‐wave Doppler ultrasound measurements for umbilical arteries and ascending aorta were obtained post‐gavage (GD12, GD14, GD18) on 2 fetuses/litter. RNA from the non‐decidual (labyrinthine and junctional zone) portion of placentas was isolated and processed for RNA‐seq and subsequent bioinformatic analyses, and the association between transcriptomic changes and fetal phenotypes assessed. Results: Exposure to ethanol in pregnant mice on GD10 attenuates umbilical cord blood flow transiently during gestation, and is associated with indices of IUGR, specifically decreased fetal weight and morphometric indices of cranial growth. Moreover, RNA‐seq of the fetal portion of the placenta demonstrated that this single exposure has lasting transcriptomic changes, including upregulation of Tet3, which is associated with spontaneous abortion. Weighted gene co‐expression network analysis (WGCNA) identified erythrocyte differentiation and homeostasis as important pathways associated with improved umbilical cord blood flow as gestation progresses. WGCNA also identified sensory perception of chemical stimulus/odorant and receptor activity as important pathways associated with cranial growth. Conclusion: Our data suggest that PAE perturbs the expression of placental genes relevant for placental hematopoiesis and environmental sensing, resulting in transient impairment of umbilical cord blood flow and, subsequently, IUGR. Abstract : A single episode of prenatal alcohol exposure during the critical period for the development of the murine fetal placental labyrinthine zone, transiently attenuated umbilical cord blood flow and impaired fetal and cranial growth. RNAseq analyses of the non‐decidual (labyrinthine and junctional zone) portion of placentae documented persistent transcriptomic changes at 8 days post‐exposure. Weighted gene co‐expression network analysis identified relationships between placental erythropoiesis and gestation‐related changes in umbilical cord blood flow, and between placental chemosensory processes and cranial growth.